SELEKSI POHON INDUK JENIS MERANTI (Shorea spp) PADA AREAL TEGAKAN BENIH IUPHHK-HA PT. SUKA JAYA MAKMUR KABUPATEN KETAPANG - Samsul, .; Muin, Abdurrani; Burhanuddin, . (Universitas Tanjungpura, 2016)
Shorea is an important species in Asia. Shorea much use for the material in the timber industry in Indonesia. The study entitled